Prevalence and patterns of substance use in conflict-affected settings: findings of a cross-sectional study from south-central Somalia - Ibrahim, Mohamed; Salad, Abdulwahab M.; Ndithia, James Mwangi; Francis, Kato; Noor, Zeynab; Hillow, Mohamed Aden; Md Mamunur Rahman Malik, SK (Frontiers in Psychiatry, 2026)
IntroductionThe south-central region of Somalia has faced recurrent armed conflicts, unrest and climatic shocks resulting in forced displacement, marginalization and social exclusion of the people affected by these enduring humanitarian crises. While psychological trauma and economic hardships are recognized contributors to mental health conditions and substance use, evidence on the prevalence and patterns of substance use in Somalia remains scarce. This study investigates the prevalence and patterns of substance use among populations living in conflict-affected districts of South-Central Somalia.MethodsA community-based cross-sectional study was conducted among 694 participants who were selected from three purposively selected conflict-affected districts of south-central Somalia using a multi-stage systematic random sampling procedure with probability proportion to size (PPS) technique. The study participants belonged to both host communities and living in the camps of internally displaced people (IDP). All people, both male and female aged ≥18 years living in these districts for at-least 6 months preceding the study were eligible for inclusion in the study. The study was conducted from October to December 2021. A specially designed questionnaire was used for collecting the data on socio-demographic characteristics, while the WHO Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) tool was used for collection of data on the use of psychoactive substances. Descriptive and inferential analyses were performed, and logistic regression was applied to identify socio-demographic determinants of substance use.ResultsThe overall lifetime prevalence of any substance use among the study participants was 53.60% (95% CI: 49.89%-57.31%) and the prevalence of current substance use was 51.30% (95% CI: 47.58%-55.02%). Among lifetime users, tobacco was the most commonly used substance (39.19%), followed by sedatives (37.46%), while cocaine was the least used (0.72%) substance. Males had higher odds of lifetime substance use compared to females (aOR = 7.31; 95% CI: 5.09–10.50). Participants who studied in Madrasah/Quranic school were less likely to have lifetime substance use compared to those with higher education (aOR = 0.29; 95% CI: 0.14–0.57). Those who were single showed significant association with lifetime substance use compared to married individuals (aOR=1.94; 95% CI: 1.34–2.79).ConclusionHigh prevalence of both lifetime and current illicit substance use was identified in young male people living in the conflict-affected areas of Somalia. These findings highlight the need for integrated public health and regulatory responses to address substance use conflict-affected Somali populations, alongside efforts to strengthen treatment capacity.